Utilization of Adaptive Communication in End-Of-Life Care in Intensive Care Unit During the Covid-19 Pandemic: Literature Review - Ulfah Nurrahmani (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
Covid-19 is becoming a global pandemic that presents new challenges in critical care. Visitation restrictions and isolation are major challenges in end-of-life care communication. The use of communication as an indicator of the quality of end-of-life care in the critical care management chain is required to adapt creatively and effectively. The aim of this research is to know the description of communication in end-of-life care in intensive care units during the covid-19 pandemic based on literature sources related to scientific research journals. The research was conducted by searching for research results published in 2019-2021 from databases such as PubMed, google scholar, and science direct using the keywords